2017
DOI: 10.1039/c7dt00894e
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the different roles of polyoxometalates in their interaction with amino acids, peptides and proteins

Abstract: One of the most attractive areas in inorganic chemistry is the synthesis of polyoxometalates (POMs) exhibiting new properties and applications. Since the impact of POMs in biochemistry and related fields of research has increased in the last few years, there has been a special interest in this topic. Significant progress in biological applications has been made where the interaction of POMs with amino acids, peptides and proteins is relevant. Versatile POMs play a series of different roles in the interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 190 publications
0
82
0
Order By: Relevance
“…The individual oligonuclear oxo‐hydroxo complexes are generally denoted by a term Poly‐oxo‐metalates (POMs). In the literature there are available a number of examples of protein and peptide complexes of POMs, derived mostly from the most acidic oxo‐vanadic and oxo‐molybdic acids. Characterization of their bonding to peptides has never been the major aim of the structure studies even if a number of reviews has recently drawn the attention to this aspect , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual oligonuclear oxo‐hydroxo complexes are generally denoted by a term Poly‐oxo‐metalates (POMs). In the literature there are available a number of examples of protein and peptide complexes of POMs, derived mostly from the most acidic oxo‐vanadic and oxo‐molybdic acids. Characterization of their bonding to peptides has never been the major aim of the structure studies even if a number of reviews has recently drawn the attention to this aspect , …”
Section: Introductionmentioning
confidence: 99%
“…Characterization of their bonding to peptides has never been the major aim of the structure studies even if a number of reviews has recently drawn the attention to this aspect. [15,16] We felt thus a challenge to produce a comparison of structure and reactivity of the complexes of structurally identical but chemically different POMs with simple peptide and amino acid model substances. Here, we report the results of interaction of simple Keggin POMs derived from Mo and W with the structurally simplest peptide glycylglycine, GlyGly, and amino acid arginine, Arg, often present as fragments in specific binding sites of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides are suitable pendants for POMs and can be covalently grafted via amide bonds . On the other hand, as observed for the targeted proteins mentioned above, they can also establish multiple weak interactions with the POM surface, being these usually more efficient upon increasing of size and charge density of the polyanion, or when using transition metal‐substituted POMs with free coordination positions on the metal ions …”
Section: Introductionmentioning
confidence: 99%
“…In addition, POMs are also used in protein crystallography. [28,29] Polyoxometalates have made great achievements in the field of enzyme inhibitors. It is reported that polyoxometalates have significant effects on the activities of nucleosidase, phosphatase, sulfate transferase, sialic acid transferase, acetylase, nuclease and protease.…”
Section: Introductionmentioning
confidence: 99%